2004
DOI: 10.1080/16501970410023461
|View full text |Cite
|
Sign up to set email alerts
|

Functional status and muscle strength in people with duchenne muscular dystrophy living in the community

Abstract: Activities of daily living in patients with Duchenne muscular dystrophy are related to age and muscle strength, and manual muscle testing grade 3 is an important cut-off point to predict their disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 17 publications
2
42
0
10
Order By: Relevance
“…The use of computer visualised incentives led to an improvement in function of spirometry testing in those shown to have a moderate intellectual or behavioural disturbance (Gauld et al 2005). Additionally, Uchikawa et al (2004) found in a group of 7 -14 year old boys with DMD living in the community, that motor scores were higher in those with good cognitive functioning compared to those with impaired cognitive functioning, even though muscle strength was not significantly different. The authors note that poor cognitive functioning has an adverse effect on activities of daily living in DMD and that this impacts training and performance of these activities.…”
Section: Functional Evidence Of Cns Aberrations In Dystrophinopathymentioning
confidence: 90%
“…The use of computer visualised incentives led to an improvement in function of spirometry testing in those shown to have a moderate intellectual or behavioural disturbance (Gauld et al 2005). Additionally, Uchikawa et al (2004) found in a group of 7 -14 year old boys with DMD living in the community, that motor scores were higher in those with good cognitive functioning compared to those with impaired cognitive functioning, even though muscle strength was not significantly different. The authors note that poor cognitive functioning has an adverse effect on activities of daily living in DMD and that this impacts training and performance of these activities.…”
Section: Functional Evidence Of Cns Aberrations In Dystrophinopathymentioning
confidence: 90%
“…In our previous study, 3 eating was the easiest item, followed by bowel management and locomotion. In the current study, locomotion was the easiest item, followed by bowel management and eating.…”
Section: Discussionmentioning
confidence: 99%
“…We also calculated the percentage of patients who were independent (scored at 6 or 7) for each FIM item (% independence), which was used as an indicator of item difficulty in a previous study. 3 Furthermore, we compared item difficulty, indicated as % independence, between patients aged ≥15 years and those <15 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that there is a negative correlation between manual muscle test results and FIM results in studies performed [194]. The manual muscle test score of 3 is a critical threshold value.…”
Section: Training For the Activities Of Daily Living And Adaptive Appmentioning
confidence: 99%